(untitled) (Journal of actual problems of jurisprudence, 2018)
This article is devoted to analysis of penal policy in the Republic of Kazakhstan. The aim of the article is research in solving the existing problems on the impact of social influence on the domestic prison system, the role of this mechanism in the process of correction of convicts. The content of the article is based on research Ph.D. Zhamuldinov V.N., which is one of well-known domestic legal scholars in the field of criminology and penal system. In addition, the paper describes the scientific and social activities of jubilee, and his brief biography. Scientific work is based on the research of Kazakhstani and foreign authors on the improvement of the penitentiary system in the process of formation of civil society and the rule of law in the Republic of Kazakhstan. Key words: law, anniversary, science, society, democratic state, civil society, the correction of convicts, social impact, personality, educational influence.